Rehabilitation Exercises and their Effect On Balance After Anterior Cruciate Ligament Surgery In Soccer - Farhan, Ahmed; Kamel, Ahmed (Journal of Physical Education, 2019)
The aim of the research is to design rehabilitation exercises and identifying their effect of balance and concentration. The researchers used motor range exercises during the first week and balance in the second week after surgery moving from easy to hard in all phases of ACL rehabilitation. The problem of the research lies in not using range of motion, balance and body weight distribution exercises immediately after surgery on the contrary they are used after weeks a matter that affect rehabilitation. The researcher hypothesized statistical differences between pre and posttests in balance in favor of posttests. The researchers used the experimental methods on (10) football players with ACL injury. The program was applied in six weeks. The researchers used range of motion exercises during the first week and balance exercises during third week after surgery due to their great role in stimulating sensory reception. The research recommended using these exercises three weeks after surgery.